In vivo differential susceptibility of sensory neurons to rabies virus infection (2013)
There is controversy with regard to the entry pathway of the rabies virus (RABV) into the central nervous system (CNS). Some authors have suggested that the virus inoculated at the periphery is captured and transported to CNS only by motor neurons; however, it has been reported that dorsal root ganglia (DRG) sensory neurons capture and transport the virus to the spinal cord (SC) and then to the brain. It is probable that preferences for one pathway or another depend on the site of inoculation and the post-infection time. Therefore, in the present study, we evaluated different vertebral segments and post-infection times, along with the location, number, and subpopulation of sensory neurons susceptible to infection after inoculating RABV in the footpads of adult mice. It was noted that the virus inoculated in the footpad preferentially entered the CNS through the large-sized DRG sensory neurons, while infection of the motor neurons occurred later. Further, it was found that the virus was dispersed in spinal cord trans-synaptically through the interneurons, arriving at both sensory neurons and contralateral motor neurons. In conclusion, we observed that RABV inoculated in the plantar footpad is captured preferentially by large sensory neurons and is transported to the DRG, where it replicates and is spread to the SC using transynaptic jumps, infecting sensory and motor neurons at the same level before ascending to the brain.